1987
DOI: 10.1177/00220345870660110601
|View full text |Cite
|
Sign up to set email alerts
|

Setting Stress in Composite Resin in Relation to Configuration of the Restoration

Abstract: The setting stress in composite resins was studied as a function of restoration shape. The shape is described by the configuration factor, C, the ratio of the restoration's bonded to unbonded (free) surfaces. In an experimental set-up, the shape of the restoration was simulated by cylindrical forms of various dimensions. The shrinkage stress was measured continuously. It was shown that in most of the clinically relevant cavity configurations, the stress-relieving flow is not sufficient to preserve adhesion to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
568
4
95

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 970 publications
(677 citation statements)
references
References 9 publications
10
568
4
95
Order By: Relevance
“…It has been reported that the relief of polymerization contraction stress of resin composites is related to cavity forms [43], the flow of resin composites [44,45], the application of flexible intermediate substances [46] and placement techniques [47].…”
Section: Relief Of Stresses Generated By Polymerization Contraction mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the relief of polymerization contraction stress of resin composites is related to cavity forms [43], the flow of resin composites [44,45], the application of flexible intermediate substances [46] and placement techniques [47].…”
Section: Relief Of Stresses Generated By Polymerization Contraction mentioning
confidence: 99%
“…Only the W-cavities showed good marginal sealing in all experimental groups. Feilzer et al [43] reported that the magnitude of polymerization contraction stress is greatly affected by the configuration of a cavity, and it increased as the C-value (the ratio of bonded surface to unbonded surface) increased. It is assumed that the C-value is related to the ratio of the cavity wall length to the free surface length in the bucco-lingual sectioned surface of a cavity.…”
Section: The Effect Of Nccl Formsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only the balance between the bonded and unbonded surfaces (the so-called C factor) [16,18] rules the contraction and stress behavior of resin materials, but also the fact that some materials, when adhering to two parallel walls, are subjected to completely different internal and external stresses than when not adhered [3,4,17].…”
Section: Solubilitymentioning
confidence: 99%
“…Many materials, particularly the resin-based ones, undergo shrinkage while curing. As the E increases and interlocking of the surrounding walls keeps the material attached, internal stress will develop perpendicularly [4,10,16] and parallel [32,38,39] to the interfaces, which may finally impair the material's integrity and/or its attachment to the walls. This perpendicular stress can be mitigated at the moment -without disrupting the bond -by tooth or prosthesis deformation [4,41] or internal porosity of the luting material.…”
Section: Adhesionmentioning
confidence: 99%